(Mis-)Predicted Subjective Well-Being Following Life Events. Issue 1 (5th April 2018) - Odermatt, Reto; Stutzer, Alois
Abstract: The correct prediction of how alternative states of the world affect our lives is a cornerstone of economics. We study how accurate people are in predicting their future well-being after facing major life events. Based on individual panel data, we compare people's life satisfaction forecasts reported in the first interview after a major life event with their actual evaluations five years later on. This is done after the individuals experience widowhood, unemployment, disability, marriage, separation, or divorce. We find systematic prediction errors that seem at least partly driven by unforeseen adaptation after the first four of these events.